HISTORY OF THE LOCALIZATION OF GEMPOL PORONG YEAR 1974-2020 IN KALIPOSO VILLAGE: HISTORY OF THE LOCALIZATION OF GEMPOL PORONG YEAR 1974-2020 IN KALIPOSO VILLAGE - Siti Holifatun; Dhalia Soetopo; Agus Mursidi; Miskawi (MAN Insan Cendekia Jambi, 2021)
This study aims to determine the historical dynamics of Gempol Porong localization which is located in Kaliploso Village, Cluring District, Banyuwangi Regency. The problems studied in this research are: 1). What is the background of the establishment of Gempol Porong Localization? 2). What are the positive and negative impacts of Gempol Porong Localization for the people of Kaliploso Village? 3). What are the community's efforts to prevent the growth of Gempol Porong Localization in Kaliploso Village?. The methodology used in this research is a qualitative analysis approach, which is used to describe the Gempol Porong Localization in 1974-2020. The results of the research conducted at Gempol Porong Localization, Kaliploso Village, started from a collection of small locations located in Cawanan, Plampang, Plosorejo and Rumping. After deliberation and consideration of the establishment of localization in 1974, there was a policy from the Village Government to relocate the locations of these illegal sex workers to remote areas of Cangkring away from the crowds, at that time they were still under the Tampo Village Administration. The year 1998 became a new historical finding regarding the division of the Village, where Dusun Plosorejo carried out the division of the territory, becoming the Village of Kaliploso. The policy shifts to Kaliploso Village to oversee the growth and development of the Gempol Porong Localization. The dynamics of Gempol Porong localization have changed from a social and economic perspective. In 1974-2020 the localization experienced ups and downs of changes from an increase in the economy, changes in lifestyle (clothing, home design and health care). The 2011 policy on localization closures issued by Banyuwangi Regent Regulation No. 88 of 2011. Impact on the income of dependent people. Therefore, the government must also provide a solution with the closure. Various efforts have been made by the community to break the chain of localization development by providing health education conducted by the health authorities, creativity training and child assistance by volunteers to provide education about protecting themselves to avoid sexual crimes